Isolation of highly pathogenic H5N6 avian influenza virus in Southern Vietnam with genetic similarity to those infecting humans in China. Issue 6 (30th July 2019) - Tsunekuni, Ryota; Sudo, Kasumi; Nguyen, Phuong Thanh; Luu, Bach Duc; Phuong, Thai Duy; Tan, Tran Minh; Nguyen, Tung; Mine, Junki; Nakayama, Momoko; Tanikawa, Taichiro; Sharshov, Kirill; Takemae, Nobuhiro; et al.
Abstract: Since 2013, H5N6 highly pathogenic avian influenza viruses (HPAIVs) have been responsible for outbreaks in poultry and wild birds around Asia. H5N6 HPAIV is also a public concern due to sporadic human infections being reported in China. In the current study, we isolated an H5N6 HPAIV strain (A/Muscovy duck/Long An/AI470/2018; AI470) from an outbreak at a Muscovy duck farm in Long An Province in Southern Vietnam in July 2018 and genetically characterized it. Basic Local Alignment Search Tool (BLAST) analysis revealed that the eight genomic segments of AI470 were most closely related (99.6%–99.9%) to A/common gull/Saratov/1676/2018 (H5N6), which was isolated in October 2018 in Russia. Furthermore, AI470 also shared 99.4%–99.9% homology with A/Guangxi/32797/2018, an H5N6 HPAIV strain that infected humans in China in 2018. Phylogenetic analyses of the entire genome showed that AI470 was directly derived from H5N6 HPAIVs that were in South China from 2015 to 2018 and clustered with four H5N6 HPAIV strains of human origin in South China from 2017 to 2018. This indicated that AI470 was introduced into Vietnam from China. In addition, molecular characteristics related to mammalian adaptation among the recent human H5N6 HPAIV viruses, except PB2 E627K, were shared by AI470. These findings are cause for concern since H5N6 HPAIV strains that possess a risk of human infection have crossed the Chinese border.